Changes in Human Milk Fat Globule Composition Throughout Lactation: A Review - Thum, Caroline; Wall, Clare; Day, Li; Szeto, Ignatius M. Y.; Li, Fang; Yan, Yalu; Barnett, Matthew P. G. (Frontiers in Nutrition, 2022)
There has been a growing interest in understanding how the relative levels of human milk fat globule (MFG) components change over the course of lactation, how they differ between populations, and implications of these changes for the health of the infant. In this article, we describe studies published over the last 30 years which have investigated components of the MFG in term milk, focusing on changes over the course of lactation and highlighting infant and maternal factors that may influence these changes. We then consider how the potential health benefits of some of the milk fat globule membrane (MFGM) components and derived ingredients relate to compositional and functional aspects and how these change throughout lactation. The results show that the concentrations of phospholipids, gangliosides, cholesterol, fatty acids and proteins vary throughout lactation, and such changes are likely to reflect the changing requirements of the growing infant. There is a lack of consistent trends for changes in phospholipids and gangliosides across lactation which may reflect different methodological approaches. Other factors such as maternal diet and geographical location have been shown to influence human MFGM composition. The majority of research on the health benefits of MFGM have been conducted using MFGM ingredients derived from bovine milk, and using animal models which have clearly demonstrated the role of the MFGM in supporting cognitive and immune health of infants at different stages of growth and development.